Bistable, Pneumatically Actuated Microgripper Fabricated Using Two‐Photon Polymerization and Oxygen Plasma Etching. (20th January 2023) - Power, Maura; Barbot, Antoine; Seichepine, Florent; Yang, Guang-Zhong
Abstract : Fabrication of actuatable micromechanisms onto the tip of submillimeter medical instruments permits microsurgery, cellular‐level intervention, targeted drug delivery, or placement of microimplants. In these systems, a common lack of integrated microsensors or optical feedback prohibits stabilizing closed‐loop control. Moreover, the low stiffness of compact actuator and microfabrication limitations lead to difficult control. Herein, a compact bistable open‐loop micromechanism mounted on a small (170 μm) capillary fiber is developed. Bistabillity is utilized to control the mechanism to precise positions without the need for feedback or continuous control. Repeatable fabrication of this compact and high‐resolution bistable micromechanism is achieved with a two‐photon polymerization (2PP) process refined by oxygen plasma etching (OPE) that results in minimal feature size of a few hundred nanometers along the direction of the laser's axis, allowing 2PP bistable mechanisms to be fabricated in arbitrary orientations not restricted by printing direction. Finite element method simulations and experimental studies of the OPE effect are presented and used to optimize the micromechanism's bistable behavior. Finally, the feasibility of such compact bistable mechanism with a gripper that captures 50 μm spheres and passively maintains grasping without constant driving force even in long open‐close cycles is demonstrated. Abstract : The fabrication of a bistable tethered microgripper is demonstrated. To achieve repeatable and consistent fabrication of compact and high‐resolution micromechanism, a process of two‐photon polymerization (2PP) refined by oxygen plasma etching is used. The resulting feature size is a few hundred nanometers along the laser direction allowing 2PP bistable mechanisms to be fabricated in orientations not restricted by printing direction.